Phyllodistomum centropomi sp. n. (Digenea: Gorgoderidae), a parasite of the fat snook, Centropomus parallelus (Osteichthyes: Centropomidae), in the Papaloapan River at Tlacotalpan, Veracruz State, Mexico - Mendoza-Garfias, Berenit; de León, Gerardo Pérez-Ponce (Zootaxa, 2005)
Phyllodistomum centropomi n. sp. (Digenea: Gorgoderidae) is described from the urinary bladder of Centropomus parallelus (Osteichthyes: Centropomidae) from the Papaloapan River in Veracruz State, Mexico. This species is distinguished from its congeners in North America, either marine or freshwater, in having the vitelline glands located in a posterolateral position to the ovary and the margin of the hindbody possessing slight undulations with muscular indentations from the level of testes to the posterior end of the body. The new species most closely resembles P. mayesi Brooks & MacDonald, 1986, a parasite of Trachycorystes insignis in the Río Atrato, in the vicinity of Quibdo, Choco, Colombia, since both possesses postovarian paired vitelline glands, but P. centropomi differs by having muscular undulations on the margin of hindbody and an oral sucker/acetabulum ratio close to unity.